Expression of Her-2/neu in extrahepatic cholangiocarcinoma - Shamekh R; Rosa M; Sayegh Z; Ghayouri M; Kim R; Malafa MP; Coppola D (Dove Medical Press, 2017)
Rania Shamekh,1,* Marilin Rosa,2,* Zena Sayegh,2 Masoumeh Ghayouri,2 Richard Kim,3 Mokenge P Malafa,3 Domenico Coppola2 1Department of Pathology, University of South Florida, 2Department of Anatomic Pathology, 3Department of Gastrointestinal Oncology, H. Lee Moffitt Cancer Center & Research Institute, Tampa, FL, USA *These authors contributed equally to this work Background: Receptor tyrosine-protein kinase erbB-2, which is also frequently called human epidermal growth factor receptor-2 (Her-2) or Her-2/neu, has been found to be overexpressed in various human cancers.Hypothesis: The aim of this pilot study was to explore the frequency of Her-2/neu gene amplification and protein expression in extrahepatic cholangiocarcinoma (EHBC). We used the World Health Organization classification criteria for EHBC.Materials and methods: This was a retrospective study using 88 tissue samples, including 45 samples from non-neoplastic biliary tissue (NNB) and 43 samples of extrahepatic cholangiocarcinoma (EHBC). A tissue microarray including NNB and EHBC was constructed and analyzed by immunohistochemistry (IHC) and dual in situ hybridization for Her-2/neu protein expression and amplification, respectively. The Her-2/neu expression was scored following the guidelines used for the ToGA study.Results: All NNB samples and all but one EHBC samples showed no expression of Her-2/neu by IHC. The one EHBC case immunohistochemically positive for Her-2/neu had an IHC score of 3+. Her-2/neu gene amplification was present in two EHBC samples only and included the case found to be positive by IHC.Conclusion: Our findings are similar to those reported in the literature. Although Her-2/neu overexpression has been documented in many types of cancer, Her-2/neu protein overexpression tends to have no role in the development and/or progression of EHBC. Keywords: extrahepatic, cholangiocarcinoma, Her-2/neu, ToGA, immunohistochemistry